Asymmetry in Power Relations and the Role of the LPSK in Protecting Justice Collaborators: An Empirical Study of Criminal Cases Involving Law Enforcement Officials in Palangka Raya - Herna Fitriani; Novea Elisya Mawarni; Fransisco Fransisco; Heriamariaty Heriamariaty; Mulida Hayati; Rico Septian Noor (Fakultas Syariah Universitas Islam Negeri Sultanah Nahrasiyah Lhokseumawe, 2026)
This study was prompted by a criminal case in Palangka Raya City involving a cooperating witness (Justice Collaborator) who faced intimidation during the law enforcement process. This situation highlights asymmetrical power relations that potentially hinder investigations and reduce the effectiveness of legal protection. This study aims to analyze the legal considerations of the Witness and Victim Protection Agency (LPSK) in designating MH as a Justice Collaborator and to examine the role of the LPSK in providing protection during the trial process at the Palangka Raya District Court. Employing an empirical legal method with a qualitative approach, data were collected through interviews with an expert staff member of the LPSK’s Protection Bureau and the Chair of the Genta Keadilan Legal Aid Institute, who served as MH’s legal counsel. The findings indicate that MH’s designation as a Justice Collaborator was based on the fact that he was not the principal perpetrator, the importance of his testimony in uncovering the offense, his good faith, and the need for protection due to intimidation and psychological trauma. The protection provided by the LPSK includes physical, psychological, legal, and family protection, enabling the witness to testify freely and safely throughout the judicial process. Theoretically, this study reinforces research on the importance of protecting Justice Collaborators in power imbalances, demonstrating that legal protection effectiveness depends on institutional implementation rather than statutory norms alone. Practically, these findings serve as an evaluative basis for the LPSK and law enforcement to strengthen protection mechanisms in cases involving unequal power dynamics.